Pedagogical Content Knowledge and Content Knowledge of Prospective Geography Teachers on Digitality and Geography Classrooms: Development of Self-Assessment Scales and First Results - Schubert, Jan Christoph; Velling, Hanna (Journal of Geography Education, 2025)
Regarding digitality, the qualification of geography teachers is important. However, economically usable instruments for measuring as well as findings on the pedagogical content knowledge (PCK) and content knowledge (CK) of teachers with regard to digitality and geography classrooms are lacking. Therefore, item-based self-assessment scales for PCK and CK were developed and used with n = 231 future geography teachers. After analyzing the latent structures using EFA, the extent of knowledge was examined using inferential statistics. There are solid indications of the suitability of the developed scales in terms of reliability and validity and the students' PCK is only average.
Keywords: content knowledge, pedagogical content knowledge, digitality, item development, exploratory factor analysis